Implementasi Mikrokontroler ESP8266 sebagai Sensor Berat dan Jumlah Orang pada Beban Jembatan - Sri Aji Eka Mahendra; Subairi Subairi; Nachrowie Nachrowie; Delila Cahya Permatasari; Sulistiyanto Sulistiyanto; Syifaul Fuada (Universitas Merdeka Malang, 2023)
Damage to the bridge resulted in disruption of the activities of residents who want to cross the bridge. Damage to the bridge is not only due to problems with the infrastructure but can also be caused by humans, one of which is due to excess capacity on the bridge so that the construction of the bridge cannot hold or accommodate many people resulting in the bridge collapsing and resulting in several fatalities. This research is expected to help reduce and prevent damage to the bridge structure by implementing a Load Sensor using the ESP8266 microcontroller. This system is based on the Internet of Things (IoT). Based on the research results, when the condition of the bridge has no visitors, the resulting weight is 0, the display on the serial monitor